Evaluasi Kinerja Penyuluh Pertanian dalam Mewujudkan Implementasi Paket Teknologi di Kecamatan Makale Kabupaten Tana Toraja - Yosep Paningo; Ibrahim, Helda; nursaman, herman (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Global challenges such as climate change and land degradation demand the strengthening of the agricultural sector through the adoption of relevant technologies. Agricultural extension plays an important role in conveying information and technological innovations to farmers, with extension workers as facilitators, educators, and motivators in accelerating the implementation of agricultural technology packages. However, the rate of adoption of technology by farmers is still low, especially in Tana Toraja Regency, South Sulawesi. In addition, there is no comprehensive and results-based evaluation system for extension workers. This study aims to determine the level of farmers' understanding of agricultural technology packages introduced by agricultural extension workers in Batu Papan Village, Makale District, Tana Toraja Regency. The research uses a descriptive quantitative approach with the object of the study, namely Field Agricultural Extension Workers (PPL) active in Makale District as many as seven people and 139 assisted farmers from six farmer groups. Farmer samples were taken as much as 20% of the population or 30 respondents using census and purposive sampling techniques. Data collection was carried out through a questionnaire with a Likert scale to assess farmers' perception and level of understanding of the implementation of agricultural technology packages. The results showed that the level of farmers' understanding of the technology package introduced by extension workers was in the "very high" category with an index value of 82.6%. These findings show that extension workers have an effective role in increasing farmers' knowledge and involvement. Therefore, it is necessary to strengthen the support of extension facilities and infrastructure, such as technological teaching aids, audiovisual media, and field transportation, to support the optimization of the performance of agricultural extension workers in the region.